Políticas educacionais para a educação indígena no Planalto santareno - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The present work called “Educational policies for indigenous education in the Santarém plateau aims to understand the importance of promoting reflection on government actions that involve indigenous education in the municipality of Santarém, especially in the Santarém plateau; It also aims to highlight how indigenous educational policies, which must be differentiated and which began in 2004, are implemented in the Santarém plateau, essentially, in the indigenous school education of the Munduruku peoples. In this sense, the author's object of investigation focused on the search to demonstrate how the right to differentiated indigenous education can, in fact, be guaranteed to these people in the municipality of Santarém. The study is qualitative and is characterized and developed by ethnographic research with data collection, which adopted procedures such as participatory research and, as instruments, the field interview, notebook for notes. The research interlocutors are the residents of the villages investigated, that is, leaders (director, indigenous and non-indigenous teachers). This criterion for choosing the categories was based on the understanding that all these social actors participate directly and indirectly in the process of indigenous school education at school and in the village, leadership has an important meaning and is a fundamental skill for the manager and his students in the school environment, which significantly contributes to the development of the education process. In this sense, the history of indigenous education faces the challenges and demands of observation that the participants presuppose two moments: HISTORICAL ISSUES AND POLICIES OF THE FEDERAL GOVERNMENT THE FIRST MOMENT the researchers the first moment and with the colonial period which aimed to assimilation of indigenous peoples and strengthening with the federal constitution in the 70s, which was a strengthening for indigenous peoples. It is the second moment INDIGENOUS EDUCATION FROM THE LOOK OF THE MANAGEMENT OF THE T.I. MUNDURUKU PLANALTO POLE seeking the importance of indigenous education for these people. Therefore, the text carries out a brief bibliographical reflection on the indigenous education of the Munduruku people, given that indigenous education is in the process of understanding educational policies considering their perspectives on difference education.
Keywords: Educação indígena; Planalto santareno; Educação diferenciada; CNPQ:: CIÊNCIAS HUMANAS